Profil Populasi Sapi Pesisir Di Kabupaten Pesisir Selatan Sumatera Barat - Sarbaini Sarbaini; R. Angraini; R. Suhati; A. Husni (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
The purpose of the present study was to estimate the population characteristics of the Pesisir cattle in Pesisir Selatan district of the West Sumatera province. Purposive sampling procedure was used to collect data from 484 farmers rearing about 1341 Pesisir cattle in Pesisir Selatan. The data were statistically analyzed descriptively. Results of the study showed that ratio of male to female was 1 : 7. The population was dominated by females with the age of more than 3 years (35,72%), while the lowest (0.89%) was the male at more than 3 years of age. The rate of calving, calving percentage, and percent of died were 24.09%, 49.85%, and 1,98%, respectively.